Compare between simex and Quassi-likelihood methods in estimation of regression function in the presence of measurement error - حمود السامرائي مناف يوسف; جابر احمد مهدي (Journal of Economics and Administrative Sciences, 2019)
In recent years, the attention of researchers has increased of semi-parametric regression models, because it is possible to integrate the parametric and non-parametric regression models in one and then form a regression model has the potential to deal with the cruse of dimensionality in non-parametric models that occurs through the increasing of explanatory variables. Involved in the analysis and then decreasing the accuracy of the estimation. As well as the privilege of this type of model with flexibility in the application field compared to the parametric models which comply with certain conditions such as knowledge of the distribution of errors or the parametric models may not represent the phenomenon properly studied. In this paper, we will show semi-parametric methods in estimation of regression function in the presence of measurement error, and these methods are Simex method and Quasi-likelihood method and will be comparing between this methods by using (MASE) criterion. A simulation had been used to study the empirical behavior for the semi-parametric models, with different sample sizes and variances. The results using represent that the instrument variable is better than Simex method at different sample sizes and variances that been used.